Réponses

  • Utilisateur Brainly
2014-04-26T19:38:23+02:00
M= (-3)²-[2-5x(3-7)]                          N= 5/7-2/7/(-3)
   = 9-[2-(5x3)-(5x(-7))]                        = 5/7-2/21
   = 9-[2-15+49]                                  = 5x3/7x3-2/21
   = 9-2+15-49                                   = 15/27-2/21
   =-27                                              = 13/21
Meilleure réponse !
2014-04-26T19:42:16+02:00
M= (-3)² - [ 2 - 5 x ( 3- 7 ) ]
M= 9 + 2 + 5 x -4
M= 11 + ( -20 )
M= -13

N=  \frac{5}{7} -  \frac{2}{7} ÷ 3
N=  \frac{5}{7} -  \frac{2}{21}
N= \frac{13}{21}


__________________



P=  \frac{600}{300000}
P= \frac{1}{500}